HERMENEUTIC INTERPRETATION AS A FRAMEWORK FOR MEANING RECONSTRUCTION IN TRANSLATION STUDIES (World Bulletin of Education and Learning, 2025)
This article explores hermeneutic interpretation as a foundational framework for understanding how meaning is reconstructed in translation. Building on philosophical hermeneutics and contemporary translation theory, the study argues that translation is an interpretive act shaped by the translator’s historical horizon, cultural knowledge, and linguistic intuition. Hermeneutics provides a methodological lens for analyzing ambiguity, polysemy, intertextuality, and cultural embeddedness within source texts. The article highlights the centrality of the hermeneutic circle, the fusion of horizons, and the dialogic nature of understanding as key processes that guide translators in negotiating meaning across languages. These principles are examined through their relevance to literary, technical, and audiovisual translation, demonstrating how interpretive competence influences decisions on equivalence, style, and cultural mediation. The article concludes that hermeneutics deepens translation studies by clarifying the cognitive and ethical dimensions of translational judgment and by offering a robust conceptual basis for analyzing how translators construct meaning in multilingual communication.
Keywords: Hermeneutics, translation studies, meaning reconstruction, interpretation, equivalence, cultural mediation, hermeneutic circle, fusion of horizons, translator agency.